An online healthy relationship tool and safety decision aid for women experiencing intimate partner violence (I-DECIDE): a randomised controlled trial. (June 2019) - Hegarty, Kelsey; Tarzia, Laura; Valpied, Jodie; Murray, Elizabeth; Humphreys, Cathy; Taft, Angela; Novy, Kitty; Gold, Lisa; Glass, Nancy
Summary: Background: Evidence for online interventions to help women experiencing intimate partner violence is scarce. We assessed whether an online interactive healthy relationship tool and safety decision aid (I-DECIDE) would increase women's self-efficacy and improve depressive symptoms compared with an intimate partner violence information website. Methods: In this two-group pragmatic randomised controlled trial, we enrolled women who had screened positive for any form of intimate partner violence or fear of a partner in the 6 months before recruitment. Women aged 16–50 years currently residing in Australia, who had safe access to a computer and an internet connection, and who answered positively to one of the screening questions in English were eligible for inclusion. Participants were randomly assigned (1:1) by computer to receive either the intervention or control website. The intervention website consisted of modules on healthy relationships, abuse and safety, and relationship priority setting, and a tailored action plan. The control website was a static intimate partner violence information website. As the initial portion of the website containing the baseline questions was identical for both groups, there was no way for women to tell which group they had been allocated to, and the research team were also masked to participant allocation until after analysis of the 12-month data. Data were collected at baseline, immediately after completion of the website, at 6 months, and 12 months. Primary outcomes were mean general self-efficacy score (immediately after website completion, and at 6 months and 12 months) and mean depression score (at 6 months and 12 months). Data analyses were done according to intention-to-treat principles, accounting for missing data, and adjusted for outcome baseline scores. This trial was registered with the Australian New Zealand Clinical Trials Registry, ACTRN 12614001306606. Findings: Between Jan 16, and Aug 28, 2015, 584 patients registered for the study and were assessed for eligibility. 422 eligible participants were randomly allocated to the intervention group (227 patients) or control group (195 patients). 179 (79%) participants in the intervention group and 156 (80%) participants in the control group completed 12-month follow-up. Mean self-efficacy at 6 months and 12 months was lower for participants in the intervention group than for participants in the control group, although this did not meet the prespecified mean difference (6 months: 27·5 [SD 5·1] vs 28·1 [4·4], imputed mean difference 1·3 [95% CI 0·3 to 2·3]; 12 months: 27·8 [SD 5·4] vs 29·0 [5·0], imputed mean difference 1·6 [95% CI 0·5 to 2·7]). We found no difference between groups in depressive symptoms at 6 months or 12 months (6 months: 22·5 [SD 17·1] vs 24·2 [17·2], imputed mean difference −0·3 [95% CI −3·5 to 3·0]; 12 months: 21·9 [SD 19·3] vs 21·5 [19·3], imputed mean difference −1·9 [95% CI −5·6 to 1·7]). Qualitative findings indicated that participants found the intervention supportive and a motivation for action. Interpretation: Our findings highlight the need for further research, development, and refinement of online interventions for women experiencing intimate partner violence, particularly into the duration needed for interventions. Although we detected no meaningful differences between groups, our qualitative results indicated that some women find an online tool a helpful source of motivation and support. Funding: Australian Research Council.